Introduction of giant tortoises as a replacement "ecosystem engineer" to facilitate restoration of Santa Fe Island, Galapagos. Issue 1 (6th July 2021) - Tapia, Washington; Goldspiel, Harrison B.; Gibbs, James P.
Abstract : Re‐establishment of ecosystem engineers via introduction of replacement species is increasingly being proposed to facilitate ecosystem restoration of island ecosystems around the world, yet attendant challenges and risks remain largely unknown. We evaluate the first phase (2015–2020) of a program to restore a population of giant tortoises, ecosystem engineers of terrestrial ecosystems of the Galapagos Islands, to Santa Fe Island during which a total of 551 juvenile and 31 subadult tortoises of the non‐native Española Island species ( Chelonoidis hoodensis ) were translocated. After 5 years, most (85%) of tortoises released remain alive, exhibiting robust vital rates comparable to those of conspecifics in their native range, having colonized 10% of the island via gradual dispersal from the point‐of‐release. Populations of an arboreal cactus ( Opuntia echios )—a keystone species for many organisms on the island and intended beneficiary of tortoise restoration—and pallid land iguanas ( Conolophus pallidus )—an endemic, herbivorous reptile considered potentially at risk from the introduction of tortoises, both increased coincident with the arrival of tortoises. Herbivore exclosure experiments revealed that the island's plant community manifested a response to the arrival of tortoises; however, significant engineering of the island's vegetation will require many decades. These results highlight the first stage of what appears to be a successful conservation intervention that can serve as a "proof of concept" for introduction of ecological replacements to other islands in Galapagos, and potentially for other island ecosystems around the world.